2020
DOI: 10.1590/1414-431x20209290
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of increased expression of RBM8A in gastric cancer

Abstract: This study was designed to investigate the expression of RBM8A protein in patients with gastric cancer (GC) and to explore its correlation with clinical pathological features as well as prognosis. One hundred pairs of gastric carcinoma tissues and adjacent tissues from patients undergoing gastrectomy for GC were included in this study. The protein expression level of RBM8A was determined by immunohistochemistry using tissue microarrays. We also detected the mRNA expression level of RBM8A in 16 pairs of gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…For example, microarray and RT-qPCR results revealed an elevated level of RBM8A in primary cervical tumor tissues and were helpful on predicting lymph node metastasis (Kim et al 2008). Similarly, higher RBM8A mRNA level was observed in hepatocellular carcinomas and gastric cancers, which is correlated with advanced TNM stage and poor overall survival (Lin et al 2019;Lv and Cheng 2020). Nevertheless, the clinical significance of RBM8A in colon adenocarcinoma has not been illustrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, microarray and RT-qPCR results revealed an elevated level of RBM8A in primary cervical tumor tissues and were helpful on predicting lymph node metastasis (Kim et al 2008). Similarly, higher RBM8A mRNA level was observed in hepatocellular carcinomas and gastric cancers, which is correlated with advanced TNM stage and poor overall survival (Lin et al 2019;Lv and Cheng 2020). Nevertheless, the clinical significance of RBM8A in colon adenocarcinoma has not been illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, RBM8A-depleted A549 cells showed impaired cell cycle progression and subsequently resulted in poor cell proliferation capacity (Ishigaki et al 2013a). Increased expression of RBM8A was later identified in hepatocellular carcinoma (HCC) and gastric cancer, which was correlated with poorer prognosis (Lin et al 2019;Lv and Cheng 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high and low expression of RBM8A showed significant differences in TNM stage and LNM of BC. Similarly, LV et al have reported that RBM8A expression is increased in gastric carcinoma tissues, and the level of RBM8A is correlated with tumor size, LNM, TNM stage, and distant metastasis in gastric cancer [ 11 ]. Therefore, we speculated that RBM8A may be an oncogene existing in BC to promote the progression of BC, which could be a promising biomarker and therapeutic target in the diagnosis and treatment of BC.…”
Section: Discussionmentioning
confidence: 99%
“…RBM8A suppression retards the proliferation of mesothelioma cells [ 10 ]. In addition, gastric cancer patients with increased RBM8A expression have lower overall survival [ 11 ]. However, the function and underlying mechanism of RBM8A in BC is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the results of Lin et al's team, Liang et al's team [ 25 , 26 ] also found that RBM8A was highly expressed in HCC tumor tissues and further proved that RBM8A promoted the migration and invasion of tumor cells in HCC by activating the epithelial-mesenchymal transformation signaling pathway. In addition to liver cancer, studies have also reported that the expression level of RBM8A in gastric cancer and colon adenocarcinoma is higher than that in adjacent tissues, and its expression level is positively correlated with tumor size, depth of invasion, and lymph node metastasis; RBM8A can also be used as an independent prognostic factor that affects the overall survival rate of patients [ 27 , 28 ]. To study the correlation between the gene expression profile of primary cervical tumor tissue and lymph nodes, Kim et al [ 29 ] screened patients with primary cervical cancer and found that RBM8A was highly expressed in lymph node metastatic lesions compared with those without cervical cancer lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%